Climate risk and green investments: New evidence. (15th February 2023) - Dutta, Anupam; Bouri, Elie; Rothovius, Timo; Uddin, Gazi Salah
Abstract: The academic literature on green energy equity markets has increased extensively over the last decade due to growing concerns about climate change and the substantial flow of investments into alternative energy markets. This study contributes by investigating the effect of climate risk on the return and volatility of green energy assets. This is one of the first papers to assess such effects using the recently developed climate policy uncertainty index as an indicator of climate risk. In particular, we seek to answer the following research questions. Firstly, does rising climate risk lead to a significant increase in green energy asset returns? Secondly, does climate risk affect the volatility of green energy assets negatively? Employing various models, we provide statistical evidence in favour of our hypotheses. Rising climate risk seems to encourage investment in alternative energy, which leads to an upward demand for green energy, which in turn increases the prices of green energy investments and decreases their volatility levels. Our analysis further shows that when climate risk increases, the correlation between crude oil and green energy returns decreases. Furthermore, green energy assets are more effective than gold for hedging oil market risk, without ignoring the hedging ability of technology stock investment. Highlights: Study the effect of climate risk on the return and volatility of green energy assets. Rising climate risk increases the prices of green energy and decreases their volatility levels. When climate risk increases, the correlation between oil and green energy returns decreases. Green assets are more effective than gold for hedging the oil market risk. The hedging ability of technology stock investment should not be ignored.